Tunable and ultra-stable UV light-switchable fluorescent composites for information hiding and storage. Issue 32 (30th July 2018) - Li, Mengxiao; Feng, Yu; Tian, Qingyong; Yao, Weijing; Liu, Li; Li, Xuan; Wang, Huanjun; Wu, Wei
Abstract : Different information could be hidden and read under 365 nm and 254 nm light excitation, respectively. Moreover, the hidden information still can be identified after being exposed to an ambient environment for as long as 90 days. Abstract : Advanced fluorescent materials have demonstrated great value in the anti-counterfeiting field for information storage and hiding. In this work, a novel strategy for producing UV light-switchable fluorescent patterns to hide and store information is proposed based on carbon dots (CDs) and Y2 O3 :Eu composites with exceptional optical properties. CDs can present blue emission under both 254 nm and 365 nm UV light excitation, but Y2 O3 :Eu can only arouse a red color under 254 nm light excitation. Under conventional 365 nm excitation, a single blue color and partial information are shown, however, the whole information in patterns can be displayed under specific 254 nm excitation. The functional anti-counterfeiting patterns are made by screen printing using as-prepared polyvinyl alcohol (PVA)-medium fluorescent inks. Moreover, the hidden information retained its integrity after printed patterns were exposed to an ambient environment for 90 days. Such invisible, tunable and ultra-stable fluorescent patterns utilizing 254 nm UV light well achieve information hiding and storage and increase information security for anti-counterfeiting applications.